ANALISIS FINANSIAL DAN STRATEGI PENGEMBANGAN BUDIDAYA JAMUR MERANG DI RAJABASA JAYA BANDAR LAMPUNG - Fiko Alif Putra; Teguh Endaryanto; Serly Silviyanti (Lampung University, 2021)
This study aims to analyze the financial viability and development strategy of straw mushroom farming in Rajabasa Jaya. This research was carried out in September 2018 in Rajabasa Jaya, Rajabasa District, Bandar Lampung City that was intentionally chosen by consideration of the straw mushroom farming being the example for the straw mushroom farming in Bandar Lampung City. Respondent in this research was the farmer in Rajabasa Jaya. The first objective was quantitative analyzed by financial analysis (Gross Benefit Cost Ratio (Gross B/C), Net B/C, Net Present Value (NPV), Internal Rate Return (IRR) dan Payback Period (PP)) with interest rate of 7% and economic life of business by 6 years. The second objective was descriptive analyzed by SWOT analysis. Based on the result, the straw mushroom farming is financially feasible because of the Gross B/C and Net B/C values of more than 1, NPV value more than 0, IRR value higher than interest rate, and PP value shorter than economic life of business. The strategy needed to develop the straw mushroom farming are to increase the production of quality mushroom, improve customer relationships, start the promotion of mushroom businesses to expand market network, and records the finance of straw mushroom farm.Key words: development strategy, financial analysis, straw mushroom